Quantification of heavy metals in lichens from the upper basin of the river bogotá (2016)
ichenic associations are used as bio-indicators because lichens are long-lived, known to be sensitive to changes in the habitat and environment, and obtain their nutrients from the atmosphere. In this study we quantified the Pb, Cr, As, Co and Cd metals absorbed by the Ramalina celastri, Usnea sp., Flavopunctelia flaventor, Teloschiste sexilis, Punctelia subrudecta, Parmotrema simulans, Ramalina complanata, Parmotrema bangii, Everniastrum columbiense, Parmotrema praesorediosum, Parmotrema reticulatum, and Heterodermial eucomela lichens gathered on the west bank of the river Bogotá, Colombia, in its upper basin near the town of Villapinzón, where the air and the health of the community on its banks have been affected for decades by the emissions of particulates into the air and shedding of waste waters into the river by the local tanning industry. The study found high levels of the bio-accumulation of Cd, Co, As and Cr in the lichens, with Pb values which range from 4.1 to 25.8 ppm, with the highest levels in Parmotrema reticulatum. The levels of Cd ranged from 0.8 to 45.7 ppm, with Parmotrema simulans showing the highest level. The levels of Co ranged from 0.8 to 6.3 ppm, with Heterodermia leucomela showing the highest bio-accumulation. The levels of As ranged from 9.8 to 76 ppm, with Heterodermia leucomela showing the highest level. And the levels of Cr ranged from 0.1 to 141.0 ppm, with the highest levels in Teloschiste sexilis. The results show a high accumulation of heavy metals in the lichens we studied, which were mainly derived from particulate material and indicate an impact on the community which livesin the area.